Mappe-Monde sur la projection réduite de mercator. - Giraldon (1800)
Map shows extent of the known world with six continents, major cities, major physical features, beginning with European and African continents on the left with Iceland and the coast of Greenland, to the coast of Europe and Africa on the far right with Iceland to the north [Iceland appears twice on the map]. Includes notes. Relief shown pictorially and by hachures. Scale not given.